2012
DOI: 10.3402/qhw.v7i0.10451
|View full text |Cite
|
Sign up to set email alerts
|

Medication use in the context of everyday living as understood by seniors

Abstract: Recognizing that older adults are among the biggest consumers of medication, and the demographic group most likely to suffer an adverse drug reaction (ADR), this paper details the findings from a recent study on how older adults come to understand medication and its related use. Using a qualitative content analysis method, semi-structured interviews were conducted with 21 individuals from British Columbia, Canada. Study participants ranged in age from 65 to 89 years (male=9, female=11). Using NVIVO® 7 software… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Some participants expressed their own and their older relatives' negative attitudes towards taking pain medicines for OA. These attitudes are common for older adults and their family caregivers and worrying about the side effects of or possible addiction to using pain medicines (Milder et al 2011, Holroyd et al 2012. These attitudes were also a barrier to older adults with OA in our study regularly taking prescribed pain medicine.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…Some participants expressed their own and their older relatives' negative attitudes towards taking pain medicines for OA. These attitudes are common for older adults and their family caregivers and worrying about the side effects of or possible addiction to using pain medicines (Milder et al 2011, Holroyd et al 2012. These attitudes were also a barrier to older adults with OA in our study regularly taking prescribed pain medicine.…”
Section: Discussionmentioning
confidence: 64%
“…, Holroyd et al . ). These attitudes were also a barrier to older adults with OA in our study regularly taking prescribed pain medicine.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Articles included 49 qualitative research studies [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 ], six articles of instrument development and psychometrics [ 59 , 60 , 61 , 62 , ...…”
Section: Methodsmentioning
confidence: 99%
“…A qualitative study exploring medication use in seniors indicated that a doctor is a trusted authority. On the basis of this trust, people felt confident that their doctor was choosing medications best suited for them [20]. The attitude of health providers is a dominant factor in patient disease management as well [21].…”
Section: Discussionmentioning
confidence: 99%